Strategi Co-Branding Skilvul Dalam Meningkatkan Brand Image Melalui Program Webinar Skilvul Bersama Tokopedia Di Instagram - Iqbal Sazili Putra; Rohmiati Rohmiati (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
Skilvul is a start-up that is developing in the field of education technology, located in Jakarta. Skilvul itself is part of the start-up company Impact Byte, both of which are engaged in education technology. Skilvul and Impact Byte both present digital technology learning products, especially coding or programming languages, but what makes Skilvul different is that Skilvul can be accessed through the website and Skilvul provides digital teaching, and the goal of Skilvul is to meet the needs of young technology-savvy people in Indonesia so that Indonesia has more digital talent in the future. The objectives to be achieved in this study are to describe/describe how the Skilvul webinar program with Tokopedia on Instagram as a Skilvul Co-Branding strategy in improving brand image. The research method used in this research is a case study, a qualitative approach. In this study, in-depth interviews with key informants and informants were conducted. In addition, observations were also made on Skillvul webinar activities held with Tokopedia both offline and online. . Co-Branding supporting factors such as Familiarity, Product Fit, Reputation, Atitude toward Co-Branding, Trust, Partner Factors, advertising campaigns, product experience, and quality attributes.